Modèle exploratoire de la dissonance et de l'harmonie ludo-narrative dans les jeux d’évasion - Antoine Taly (Laboratoire Experice, 2021)
Escape games have become very popular in recent years, with a growing focus on their narrative aspects. While immersion is presented as a salient feature of this game experience, there is a lack of models to analyze the immersion of players in an escape game. Yet, the relationship between narration and gameplay can influence players’ engagement and the feeling of immersion. We propose to combine Aarseth's narrative analysis model to identify elements of the game contributing to ludo-narrative dissonance or harmony in escape games, and the MEDIAL model to identify the resulting dimensions of players’ engagement.